Synthesis of Stable Diarylpalladium(II) Complexes: Detailed Study of the Aryl–Aryl Bond‐Forming Reductive Elimination1. Issue 32 (6th July 2016) - Gensch, Tobias; Richter, Nils; Theumer, Gabriele; Kataeva, Olga; Knölker, Hans‐Joachim
Abstract: The synthesis of diarylpalladium(II) complexes by twofold aryl C−H bond activation was developed. These intermediates of oxidative cyclization reactions are stabilized by chelation with acetyl groups while still maintaining sufficient reactivity to study their reductive elimination. Four distinct triggers were found for the reductive elimination of these complexes to dibenzofurans and carbazoles. Thermal elimination occurs at very high temperatures, whereas ligand‐promoted and oxidatively induced reductive eliminations proceed readily at room temperature. Under these conditions, no isomerization occurs. In contrast, weak Brønsted acids, such as acetic acid, lead to a sequence of proto‐demetalation, isomerization to a κ 3 ‐diarylpalladium(II) complex, and reductive elimination to non‐symmetrical cyclization products. Abstract : Diarylpalladium(II) intermediates of oxidative cyclization reactions were synthesized as stabilized chelates by twofold aryl C−H bond activation. Reductive elimination to dibenzofurans and carbazoles occurs without isomerization either thermally induced at high temperature, or ligand‐promoted or oxidatively induced at room temperature. Whereas the weak‐acid‐induced isomerization to κ 3 ‐diarylpalladium(II) complexes and reductive elimination lead to non‐symmetrical isomers.